MANEJO DA PALHADA DE CEREAIS DE INVERNO NO CONTROLE DO MOFO BRANCO DA SOJA - Feller, Leandro André (2014)
The white mold disease caused by the fungus [Sclerotinia sclerotiorum (Lib.) De Bary] is among the diseases that attack soybean, and can bring great losses in productivity. Between the recommendations for controlling the disease, there is the handling of straw, which serves as a physical barrier to the passage of light to the ground, an important factor in the germination of the pathogen carpogenic. The study was conducted at harvest 2012/2013 in Guarapuava-PR and Palmas-PR, with the aim of evaluating the winter cereals, oats, rye and triticale, which after desiccation, present the greatest ability to form straw, forming a physical barrier to the passage of light to the sclerodio and avoiding the spread of ascospores of Sclerotinia sclerotiorum. We evaluated the influence of treatment on the incidence of disease between the two regions, and the influence on productivity. Three winter cereals (oats, rye and triticale) and an area fallow without cultivation of plants for ground cover were evaluated. The experimental design was used in a randomized block design with seven replications, totaling 28 plots at each site. During the development of winter cereals, the morphological characteristics were evaluated: plant height, fresh weight and dry weight of the three winter cereals. After desiccation of winter cereals was sown soybean during development, assessments of disease incidence were conducted during the reproductive stages R5.1, R5.4 and R6. Agronomic, thousand grain weight and yield were obtained after soybean harvest. In the evaluation of morphological characters among winter cereals, rye had higher mean plant height, producing higher green mass, along with triticale, however not reflected in the final dry mass. Observed greater development of winter cereals in the region of Palmas. Passing for evaluation of soybean when evaluated number of pods per plant in the lower third, middle, top and total number of total pods per plant, no difference between treatments was observed. The development of soybean, no difference between plant population between treatments was observed. In evaluating the agronomic characteristics of soybean may notice a greater plant height in the region of Guarapuava did not differ between treatments. In assessing the thousand grain mass, there was a higher weight in this region of Palmas. As for productivity, only soybeans planted on triticale straw in the region of Palmas showed higher yield compared to the region Guarapuava, with no statistical difference in productivity between the treatments in the two regions. In the final evaluation of the incidence of S. sclerotiorum in the reproductive stage R6, it was observed, 77,66% and 76,58% less incidence of disease in soybean planted on rye straw, regarding the witness, Palmas and Guarapuava respectively. In assessing in vitro carpogenic germination was observed only in treatment coverage of 4 mm of soil.